Survival benefit of primary tumor resection for gastric cancer with liver metastasis: A propensity score-matched, population-based study - Wu, Jiayan; Yu, Jiandong; Chen, Zhiping; Zhu, Hongquan; Zhong, Chengrui; Liang, Yongling; Mai, Ziyan; Lin, Zejin; Wan, Yunle; Li, Guolin (Frontiers in Oncology, 2022)
Objectives Gastric cancer with liver metastasis (GCLM) is highly aggressive and has a poor prognosis. This study aims to evaluate the survival benefit of primary tumor resection (PTR) for gastric cancer with liver metastasis. Methods Data on patients with GCLM was extracted from the Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2015. A 1:1 propensity score matching (PSM) analysis was performed to minimize the heterogeneity between the PTR and no-PTR groups. The Kaplan–Meier method and Cox regression analysis were used to assess the impact of primary tumor resection (PTR) on overall survival (OS) and cause-specific survival (CSS). Results A total of 3,001 patients with GCLM were included, with 328 patients treated with primary tumor resection (PTR), whereas the other 2,673 patients were not. Patients with PTR had a significantly higher OS and CSS rate than those without PTR in unmatched and PSM cohorts. In an unmatched cohort, the median OS was 12.0 months (95% CI, 10 months to 14 months) for those who underwent PTR and 4 months (95% CI, 4 months to 5 months) for those without PTR; the median CSS for those who underwent PTR was 12.0 months (95% CI, 10 months to14 months) and 4 months (95% CI, 4 months to 5 months) for those without PTR, respectively. After PMS, the median OS was 12.0 months (95% CI, 10 months to 17 months) for those who underwent PTR and 7 months (95% CI, 5 months to 10 months) for those without PTR, respectively; the median CSS for those who underwent PTR was 12.0 months (95% CI, 11 months to 17 months) and 7 months (95% CI, 5 months to 8 months) for those without PTR, respectively. In addition, multivariate Cox analysis in the PSM cohort showed that PTR, age, degree of tumor differentiation, and chemotherapy were independent prognostic factors for OS and CSS in GCLM. Specifically, PTR was a significant protective factor for OS (HR: 0.427; 95% CI, 0.325 to 0.561, P <0.001) and CSS (HR: 0.419; 95% CI, 0.313 to 0.561, P <0.001). Conclusion Primary tumor resection improves the survival of gastric cancer patients with liver metastasis.